Human Resources Management in Improving Teacher Performance at Darussholihin Nahdlatul Wathan Kalijaga High School - Tawa, Arsis; Zulfakar, Zulfakar; Hakim, Lukmanul (Universitas Pendidikan Mandalika, 2025)
This research focuses on 3 aspects, namely; (1) human resource management program; (2) the level of teacher performance, and (3) the impact of implementing human resource management in improving teacher performance. This study uses a qualitative method. Data collection techniques were carried out through observation, interviews, and documentation involving the school principal, head of curriculum, and teachers at the school. The data analysis techniques used are data reduction, data presentation, and conclusion. The research results show that planning, organizing, directing, and supervising can be said to be quite good. First, planning by conducting a needs analysis and providing understanding regarding the K13 curriculum and learning tools that must be prepared by teachers. Second, organizing by placing and dividing tasks according to abilities and educational background. Third, direction is carried out by providing direction and guidance regarding the tasks and responsibilities given as well as providing motivation in the form of giving awards for teacher performance achievements. Fourth, supervision is carried out by the school principal through class visits and external supervisors. The implications of the research results suggest that the school provide training to the teacher council regarding learning media so that the process of communication and educational interaction between teachers and students can take place appropriately, try to increase the availability of facilities and infrastructure for the smooth and successful learning process, work together to improve each other. teacher performance, both from school principals, educational staff, and teaching staff, and it is hoped that everything that has been achieved can be improved.Key Words: Human Resource Management, Teacher Performance